2018
DOI: 10.1111/jfpe.12864
|View full text |Cite
|
Sign up to set email alerts
|

Traceability information modeling and system implementation in Chinese domestic sheep meat supply chains

Abstract: Traceability has become a prerequisite for ensuring meat quality and safety. It is the most critical requirement for developing a well‐structured traceability system to identify efficiently and model the traceability information need to be captured. This article identified Chinese domestic sheep meat supply chain and proposed the Petri nets and UML based modeling approach for identified traceability information and process. This approach followed the definition of state and transition in sheep meat production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…However, the authors concluded that simple IT systems could reduce risk in these enterprises through better implementation of traceability. Yan et al (2018) developed a traceability design based on the HACCP principles and established critical points. They pointed to the need to identify participants in the process request them to collect relevant information to facilitate traceability.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors concluded that simple IT systems could reduce risk in these enterprises through better implementation of traceability. Yan et al (2018) developed a traceability design based on the HACCP principles and established critical points. They pointed to the need to identify participants in the process request them to collect relevant information to facilitate traceability.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, many different system architectures and software designs have been proposed in order to realize the information traceability function in the meat product supply chain. Researchers have proposed to apply RFID technology in different fields such as wine, fish, and meat in order to realize the complete traceability of the food production chain [ 7 ], a pig slaughter data collection scheme to effectively address the issues of harsh environmental conditions and difficulty in the pig slaughter processing process [ 8 ], a Petri net-based and UML-based modeling approach to identify sheep meat traceability information and processes [ 9 ], and the use of DNA technology for traceability systems to prove the origin of Swiss meat [ 10 ]. It is clear that more researchers are focusing on the development of food traceability systems, but they are concentrating more on the technology and method research for a specific object or link and less on the hardware, the connection of various links, and the platform software to realize the whole traceability system.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have used qualitative interviews, document analysis and practical observations to map FSC processes and reveal the material flow, information flow and information loss points or CTPs (Gunawan et al, 2018;Yan et al, 2018). Two main shortcomings have been identified with these studies.…”
Section: Introductionmentioning
confidence: 99%
“…The export shrimp supply chain in Bangladesh is used to demonstrate the proposed methodology. A data collection approach combining qualitative interviews, direct observation and document analysis is adopted Yan et al, 2018). Three main supply chain actors are considered: farm, depot and processor.…”
Section: Introductionmentioning
confidence: 99%